Investigating \(^{149,152,155\And161}\)Tb Production Cross-Sections through Gd (p, xn) Tb and Gd(p,g) Tb Reactions: A Comprehensive Analysis Near and above the Threshold - Pandey, Kailash; Singh, D. P. (Current Perspective to Physical Science Research Vol. 3, 2023)
The Production cross-section of radio-isotopes; 149,152,155&161Tb have been calculated via various reactions on the Gadolinium isotopes, using nuclear model codes EMPIRE 3.2 & PACE4 based on Hausher Feshback approach and compared with TENDL-2019 library (calculated by TALYS code). The production of radio-nuclides is on a high rise in recent years because of wider application in advanced technological tools used in nuclear medicine. A fission decay mode is employed using a rotating liquid drop fission barrier routine. The code also provides event by event trace back of the entire decay sequence from the compound nucleus into any one of the exit channels. Threshold for the production of radio-isotope 149Tb through 152Gd(p, 4n) is 30 MeV (barrier height; 22.79 MeV) while for 152Tb & 155Tb through 155Gd(p, xn); x =1&4 channels are 6 & 28 MeV respectively. For 161Tb the production threshold through reaction channel 160Gd (p, \(γ\)) is around 6 MeV. Quite appreciable values of the production cross-sections of all the desired isotopes have been obtained within the studied energy range.The importance of the present calculations further increases keeping in view the scarcity of the experimental results. It may further aid to open up the new experimental opportunities for the production of this radionuclide.